Treasure island - Stevenson, Robert Louis (Oxford : Oxford university press, 2019)
"Treasure Island" is the story of a twelve-year-old boy, Jim Hawkins, who finds a treasure map that belonged to a pirate, Captain Flint. Jim and his friends travel to a faraway island and meet ex-crew members of Captain Flint, who were also looking for the treasure and take Jim as a hostage.
Level 6-8